Comparison of volumetric brain analysis in subjects with rheumatoid arthritis and ulcerative colitis - Cox, Jennifer G.; de Groot, Marius; Kempton, Matthew J.; Williams, Steven C. R.; Cole, James H. (Frontiers in Medicine, 2024)
Background: Rheumatoid arthritis (RA) and ulcerative colitis (UC) are two autoimmune diseases where patients report high levels of fatigue, pain, and depression. The effect of systemic inflammation from these diseases is likely affecting the brain, however, it is unknown whether there are measurable neuroanatomical changes and whether these are a contributing factor to these central symptoms.Methods: We included 258 RA patients with 774 age and sex matched controls and 249 UC patients with 747 age and sex matched controls in a case control study utilising the UK Biobank dataset. We used imaging derived phenotypes (IDPs) to determine whether there were differences in (1) hippocampal volume and (2) additional subcortical brain volumes between patients compared to controls and if there were common regions affected between these two diseases.Results: Patients with UC had moderately smaller hippocampi compared to age and sex matched controls (difference: 134.15 mm 3 , SD  64.76, p = 0.035). This result was not seen in RA patients. RA patients had a significantly smaller amygdala volume than age and sex matched controls (difference: 91.27 mm 3 , SD  30.85, p = 0.0021, adjusted p value = 0.012). This result was not seen in UC patients. All other subcortical structures analysed were comparable between the patients and control groups.Conclusions: These results indicate there are subcortical brain differences between UC, RA and controls but different regions of the limbic system are preferentially affected by UC and RA. This study may provide evidence for different neurodegenerative mechanisms in distinct autoimmune diseases.